2014
DOI: 10.1016/j.fob.2014.02.003
|View full text |Cite
|
Sign up to set email alerts
|

Fixation‐induced cell blebbing on spread cells inversely correlates with phosphatidylinositol 4,5‐bisphosphate level in the plasma membrane

Abstract: HighlightsProtein- but not lipid-stabilizing fixatives induce cell blebbing of spread cells.Asymmetric distribution of fixation-induced blebs coincides with that of PIP2.Fixation less readily induces blebbing on spread cells with elevated PIP2 levels.Fixation more readily induces blebbing on spread cells with lower PIP2 levels.Disruption of lipid rafts enhances fixation-induced blebbing of spread cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
19
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 35 publications
(40 reference statements)
3
19
0
Order By: Relevance
“…It has been suggested that many cytoskeleton‐interacting proteins reversibly bind PIP2 at the plasma membrane. Therefore, decreasing PIP2 level or local delocalisation could lead to destabilisation of membrane–cytoskeleton adhesions resulting in bleb formation (Zhao et al, ). The results shown here suggest that EhRho1 modulates PI3 kinase activity in E. histolytica cells.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been suggested that many cytoskeleton‐interacting proteins reversibly bind PIP2 at the plasma membrane. Therefore, decreasing PIP2 level or local delocalisation could lead to destabilisation of membrane–cytoskeleton adhesions resulting in bleb formation (Zhao et al, ). The results shown here suggest that EhRho1 modulates PI3 kinase activity in E. histolytica cells.…”
Section: Resultsmentioning
confidence: 99%
“…It has been shown that plasma membrane PIP2 affects actin cytoskeleton as well as blebbing in Dictyostelium discoideum and human umbilical vein endothelial cells. Depletion of PIP2 from plasma membrane enhanced bleb formation, whereas sequestering of PIP2 resulted in reduced bleb formation (Zatulovskiy & Kay, ; Zhao et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Human THP-1 monocytic leukemia cells, purchased from the Cell Bank of the Chinese Academy of Sciences (Shanghai, China), were differentiated to macrophages by a phorbol ester (phorbo-12-myristate-13-acetate, PMA) as previously reported (Zhao et al 2014). THP-1 cells were routinely cultured in DMEM media supplemented with 10% FBS, 100 U/ml penicillin, 100 lg/ml streptomycin, and 2 mM L-glutamine.…”
Section: Monocytes/macrophages and Cell Culturesmentioning
confidence: 99%
“…The observation that blebs extend at cortical regions that possess less PIP2 is consistent with the results of the membrane tethering experiments, which indicated that PIP2 increases the strength of adhesion between the actin cortex and cell membrane [ 38 ]. Recent observations of blebs in Xenopus primordial germ cells and of fixation-induced blebs in human leukemia cells also indicate the important role of PIP2 in bleb formation [ 41 , 42 ].…”
Section: Discussionmentioning
confidence: 99%